(untitled) (Quest Journal of Management and Social Sciences, 2020)
Background: There is special role of money in the economy due to its astonishing importance as change in the amount of it can have a significant effect on the major macroeconomic variables. Money supply is generally considered as policy-determined phenomenon. Like in all the nations, macroeconomic stability of Nepal also depends on the variation in the quantity of money. Objective: The principle objective of the study is to examine the impact of money supply on the economic growth of Nepal. Methodology: This study applies the ARDL approach to cointegration. Bounds test (F-version) has been carried out to determine the existence of long-run relationship between variables. Results: The empirical results pointed out that there is positive and significant long-term relationship between money supply and real economic growth in Nepal. Causality result reveals that there is unidirectional causality from money supply (M2) to Real GDP. The error correction term is found negative and statistically significant suggesting a correction of short-run disequilibrium within two and a half years. Conclusions: The study concludes that increase in the money supply helps to increase the real economic growth in Nepal. So, money supply and real GDP are associated in the long-run. Implications: The implication of the study is that, real economic growth in Nepal can be achieved if Nepal Rastra Bank emphasized on monetary policy instruments which help to increase the flow of money supply both in the short and long run.